β-Casein A2 affects milk renneting properties, cheese yield before and after ripening, and alters the texture of Caciotta cheese produced in field conditions - S. Faggion; L. Degano; P. Carnier; V. Bonfatti (Journal of Dairy Science)
ABSTRACT: The aim of this study was to investigate the effect of β-CN genetic variants on milk coagulation properties, curd and cheese yield, efficiency of cheesemaking, and quality of Caciotta cheese after 15 d of ripening. Thirty-three cheesemaking experiments were carried out at an on-farm pilot-scale dairy plant. For each cheesemaking day, small groups of cows were selected and milked separately to obtain 2 milk pools, 1 with high proportion of β-CN A1 and B in β-CN (A1B milk) and 1 with high proportion of β-CN A2 (A2 milk) in β-CN, respectively. Each milk pool originated from at least 2 cows and was processed into Caciotta cheese, producing 2 cheese wheels of commercial size. Differences across milk pools in milk composition, coagulation properties, curd yield measured by laboratory-scale microcheesemaking, cheese yield after stewing, brining, and 15 d of ripening, whey composition, recovery rates, as well as cheese composition, color, and texture were estimated using a set of mixed linear models including the random effect of the processing day, and the linear effects of the major sources of variation of the investigated traits. Compared with A1B milk, A2 milk had a remarkably 2.8-min longer rennet coagulation time, lower curd yield measured by microcheesemaking (−0.5%), cheese yield after stewing (−1.15%), brining (−0.92%), and 15-d ripening (−0.36%). No significant variations associated with the milk pools were observed in cheese composition, but cheese from A2 milk exhibited significantly lower green-to-red axis value (a*) and higher hue angle values compared with cheese processed from A1B milk, although these differences are not expected to be perceived by the human eye. Cheese from A2 milk was also characterized by a significantly lower hardness, springiness, chewiness, and gumminess than cheese from A1B milk. Our results indicate that use of A2 milk for cheese production leads to inferior technological properties and a less efficient cheesemaking process. More studies are necessary to investigate the effect of β-CN variants on product quality and consumer perception.